Personalized consumer motivation and repurchase intention of small medium enterprises on digital platform - Mat Sani, Amizatulhawa; Rozlan, Nor Azreen; Nizam, Nurul Zarirah; Kamarudin, Nurhayati; Abdullah, Mariam Miri; Osman, Azim Azuan (Universiti Putra Malaysia Press, 2024)
This study investigates the factors influencing consumer repurchase intentions within digital platforms of SMEs in Malacca, Malaysia. It introduces a novel framework comprising five motivational dimensions—price, promotion, innovativeness, store brand, and service quality sensitivity—to explore their relationships with repurchase intentions. Data from 300 SME consumers were collected through a structured survey. The findings revealed that consumer repurchase intentions in Malacca’s digital SME marketplace are significantly influenced by four motivational dimensions: price sensitivity, innovativeness sensitivity, store brand sensitivity, and service quality sensitivity, with innovativeness sensitivity emerging as the most influential factor. This underscores that consumers prioritize innovative features when deciding to repurchase from SMEs online, alongside factors like price, brand, and service quality. The study highlights the practical implications for digital marketing, stressing the importance of dynamic pricing, continuous innovation, strong branding, and exceptional service quality for SMEs to engage and retain customers effectively. Additionally, the study suggests avenues for future studies, including exploring demographic influences and the longitudinal evolution of consumer motivations.